Poor Biological Factors and Prognosis of Interval Breast Cancers: Long-Term Results of Bahceehir (Istanbul) Breast Cancer Screening Project in Turkey - Cabioglu, Neslihan; Guerdal, Sibel OEzkan; Kayhan, Arda; OEzaydin, Niluefer; Sahin, Cennet; Can, OEmuer; OEzcinar, Beyza; Aykuter, Goenuel; Vatandas, Guelcin; Aribal, Erkin; OEzmen, Vahit (AMER SOC CLINICAL ONCOLOGY, 2020)
PURPOSE The Turkish Bahceehir Breast Cancer Screening Project was a 10-year, organized, population-based screening program carried out in Bahceehir county, Istanbul. Our aim was to examine the biologic features and outcome of screen-detected and interval breast cancers during the 10-year study period. METHODS Between 2009 and 2019, 2-view mammograms were obtained at 2-year intervals for women aged 40 to 69 years. Clinicopathological characteristics including ER, PR, HER2-neu, and Ki-67 status were analyzed for those diagnosed with breast cancer. RESULTS In 8,758 screened women, 131 breast cancers (1.5\%) were detected. The majority of patients (82.3\%) had prognostic stage 0-I disease. Contrarily, patients with interval cancers (n = 15

11.4\%) were more likely to have a worse prognostic stage (II-IV disease

odds ratio {[}OR], 3.59, 95\% CI, 0.9 to 14.5) and high Ki-67 scores (OR, 3.14

95\% CI, 0.9 to 11.2). Interval cancers detected within 1 year were more likely to have a luminal B (57.1\% v 31.9\%) and triple-negative (14.3\% v 1\%) subtype and less likely to have a luminal A subtype (28.6\% v 61.5\%

P = .04). Patients with interval cancers had a poor outcome in 10-year disease-specific (DSS) and disease-free survival (DFS) compared with those with screen-detected cancers (DSS: 68.2\% v 98.1\%, P = .002

DFS: 78.6\% v 96.5\%, P = .011). CONCLUSION Our findings suggest the majority of screen-detected breast cancers exhibited a luminal A subtype profile with an excellent prognosis. However, interval cancers were more likely to have aggressive subtypes such as luminal B subtype or triple-negative cancers associated with a poor prognosis requiring other preventive strategies. (c) 2020 by American Society of Clinical Oncology